Ceacal Trichuriasis Presenting as Severe Iron Deficiency Anemia: A Case Report - Wani Abdul Ahad; Jawhar Ul Islam; Mohammad Mubarik Naqash; Aamir Shafi (Dr. Annil Mahajan, 2022)
Trichuriasis is an under reported and neglected helminth infection seen usually in children with poor sanitary conditions. It manifests as chronic abdominal pain, diarrhoea, constipation, rectal bleeding or prolapse as well as anemia and growth failure. This helminth infection is very rarely encountered in adults. we report a rare case of severe iron deficiency anemia in a young adult male who presenting with easy fatiguability and gross pallor and upon extensive evaluation Trichuris trichura was found adherent to ceacal wall of small intestine on colonoscopic examination. Finding no other cause for his severe anemia and dramatic response to oral mebendazole the iron deficiency was finally attributed to ceacal trichuriasis.